Design of a QKD protocol resistant to insider attacks in fully connected decentralized networks - Begimbayeva, Yenlik; Zhaxalykov, Temirlan; Akhtanov, Amir; Pashkevich, Ruslan; Ussatova, Olga; Arshidinova, Mukaddas (Eastern-European Journal of Enterprise Technologies, 2025)
This research focuses on enhancing the security of decentralized quantum key distribution (QKD) networks, where the absence of a central authority creates significant challenges such as malicious node infiltration, undetected key leakage, and unauthorized re-entry of revoked participants. Traditional authentication and trust models are insufficient for fully distributed QKD topologies, which remain highly vulnerable to insider threats and persistent compromise. To address these risks, let’s propose a layered security framework composed of three integrated components: Challenge-Response Authentication (CRA), Dynamic Trust Scoring (DTS), and Blockchain-Based Access Control (BBAC). CRA verifies node legitimacy through randomized quantum-state interactions, significantly reducing impersonation and quantum replay attacks. DTS implements real-time trust evaluation using anomaly detection to dynamically downgrade compromised nodes based on their behavioral deviations. BBAC maintains an immutable and tamper-proof trust ledger to block revoked nodes from re-entering under falsified identities and resists Sybil attacks using post-quantum cryptographic primitives. Simulation results confirm that the system improves detection rates of covert threats, ensures authentication latency under 10 ms, and reduces re-entry success to zero. The proposed architecture ensures long-term scalability and resilience, making it applicable to critical domains such as finance, national infrastructure, and military communication. This work contributes a novel, verifiable, and scalable solution to one of the most pressing open problems in distributed quantum networks